Ventriculoperitoneal Shunt Alone for Cerebrospinal Fluid Rhinorrhea With Neuroendocrine Alterations in Idiopathic Intracranial Hypertension: A Case Report and Literature Review - Peng, Deqing; Yang, Kaichuang; Wu, Cheng; Gao, Faliang; Sun, Weijun; Lu, Gang (Frontiers in Neurology, 2022)
Spontaneous skull base cerebrospinal fluid (CSF) leaks due to idiopathic intracranial hypertension (IIH) is a rare entity. These patients often present with CSF rhinorrhea, recurrent meningitis, chronic headache and visual defects, while few patients have been reported to present with neuroendocrine alterations. Endonasal endoscopic repair is the first-line treatment for these leaks at present. However, the relatively high risk of recurrence remains as the main cause of reoperation due to elevated intracranial pressure (ICP) after endoscopic surgery, and the absence of postoperative ICP management. A shunting procedure may stop the CSF leakage or relieve the symptoms in complex cases, and this is presently well-known as the last-line therapy for CSF liquorrhea. We describe a 29-year-old woman with spontaneous CSF rhinorrhea and neuroendocrine alterations due to IIH, with no previous history of trauma, tumor, or nasal surgery. The bone defect in the skull base became implicated when the site of the leak was detected by cranial magnetic resonance imaging and computed tomography (CT). The patient was successfully managed via ventriculoperitoneal shunt (VPS) alone without endoscopic repair, and the neuroendocrine alterations were resolved after the shunting procedure.